Уроженцы Литвы, погибшие в 1944–1945 гг. и захороненные на территории Полоцка - Korsak, Alesia (Acta humanitarica academiae Saulensis, 2019)
During the implementation of the strategic and tactical plans of the Polotsk offensive operation in 1944 in the territory of Polotsk about 2 thousand soldiers of the Red Army, including natives of Lithuania, died of wounds. In 1945, military units were stationed in Polotsk for subsequent dispatch to the front, including the 3rd reserve rifle brigade. About 30 people from it are buried in a mass grave in the territory of a civil cemetery “Gromy”. During verification of the inscriptions on gravestones, the place of service, the date and place of death, the reasons, and also personal data – the date and place of birth were defined. During the research, the difficulty was caused by the choice of the correct spelling of personal data in order to correct the errors and write new names. The work is based on the archival data of the Central Archive of the Ministry of Defence of the Russian Federation, as well as on the history of military burial (the process of enlargement of graves), as well as the material of the Zonal State Archive in Polotsk is used.